Development of ANIKOR Learning Media (Animated Coordination System) Biology for Grade XI SMA/MA - Nila Karinda; Dwi Kameluh Agustina; Eva Nurul Malahayati (Master Program of Biology Education, Universitas Lambung Mangkurat, 2021)
Research and development of ANIKOR learning media (Coordination System Animation) aims to determine the feasibility of ANIKOR learning media developed on the coordination system material on the SMA/MA grade XI class. This development research using the Thiagarajan model until the third stage which consists of define (define), design (planning), and develop (development). Data analysis used quantitative and qualitative analysis techniques, while the instruments used were validation questionnaires, readability and response questionnaires. The results of the feasibility test carried out by material experts were stated in the very feasible category, namely 95.44%, media experts in the appropriate category, 78.73%, IT experts in the very feasible category, 92.38%, and language experts in the very feasible category, 85. 56%. The readability test of six students obtained 82.22% very feasible category. The results of the response test to the three biology teachers obtained 89.80% very feasible category. Response test to 33 students obtained 82.02% very feasible category. Therefore, ANIKOR learning media is suitable for use in the learning process because it can train students in formulating material conclusions based on their understanding.AbstrakPenelitian dan pengembangan media pembelajaran ANIKOR (Animasi Sistem Koordinasi) bertujuan untuk mengetahui kelayakan media pembelajaran ANIKOR yang dikembangkan pada materi sistem koordinasi kelas XI SMA/MA. Penelitian pengembangan ini menggunakan model Thiagarajan sampai tahap ketiga yang terdiri dari define (pendefisien), design (perencanaan), dan develop (pengembangan). Analisis data menggunakan teknik analisis kuantitaif dan kualitatif, sedangkan instrumen yang digunakan yakni angket validasi, keterbacaan dan angket respon. Hasil uji kelayakan yang dilakukan oleh para ahli materi dinyatakan dalam kategori sangat layak yaitu 95,44%, ahli media kategori layak yaitu 78,73%, ahli IT kategori sangat layak yaitu 92,38%, dan ahli bahasa kategori sangat layak yaitu 85,56%. Uji keterbacaan terhadap enam siswa diperoleh 82.22% kategori sangat layak. Hasil uji respon terhadap tiga guru biologi diperoleh 89.80% kategori sangat layak. Uji respon terhadap 33 siswa diperoleh 82.02% kategori sangat layak. Oleh karena itu, media pembelajaran ANIKOR layak digunakan dalam proses pembelajaran karena dapat melatih siswa dalam merumuskan kesimpulan materi berdasarkan pemahamannya.